2021
DOI: 10.1002/ange.202015431
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Upgrading Lignin Derivatives to Carboxylates through Electrochemical Oxidative C(OH)−C Bond Cleavage by a Mn‐Doped Cobalt Oxyhydroxide Catalyst

Abstract: Oxidative cleavage of C(OH)ÀCb onds to afford carboxylates is of significant importance for the petrochemical industry and biomass valorization. Here we report an efficient electrochemical strategy for the selective upgrading of lignin derivatives to carboxylates by am anganese-doped cobalt oxyhydroxide (MnCoOOH) catalyst. Awide range of ligninderived substrates with C(OH)-C or C(O)-C units undergo efficient cleavage to corresponding carboxylates in excellent yields (80-99 %) and operational stability (200 h).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 72 publications
(59 reference statements)
2
18
0
1
Order By: Relevance
“…We sought to incorporate Au with a component that can supply electrophilic OH* for AORs. It is well-documented that transition metal oxyhydroxides (MOOHs) are capable of generating active oxygen species (OH* or O*) in an aqueous solution under certain anodic potential for oxidation of various organic substrates 23 . Hence, we expect that the MOOHs can cooperate with Au for AOR at higher potential.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We sought to incorporate Au with a component that can supply electrophilic OH* for AORs. It is well-documented that transition metal oxyhydroxides (MOOHs) are capable of generating active oxygen species (OH* or O*) in an aqueous solution under certain anodic potential for oxidation of various organic substrates 23 . Hence, we expect that the MOOHs can cooperate with Au for AOR at higher potential.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have demonstrated that Co 2+ oxidation is accompanied by the formation of electrophilic OH*, which showed catalytic activity for nucleophilic alcohols oxidation. 23 25 For Au/NiFeOOH (dark cyan curve in Fig. 2a ), the oxidation of Ni 2+ to Ni 3+ with possible active oxygen species generation was observed at potential (~1.47 V vs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrocatalysis can be powered by renewable energy (solar, wind, and hydro) that represents a sustainable and attractive strategy to generate clean H 2 from water at cathode and valueadded oxygenates from organic compounds at anode under mild conditions [18][19][20][21] . It has obtained great advancements in efficient and selective transformation of various organic compounds, such as simple alcohols and renewable biomass-derived oxygenates, and varieties of valuable carbonyl chemicals such as formate 22,23 , acetate 24,25 , 2,5-furandicarboxylate 26 , adipate 19 can be obtained. However, the electrocatalytic reforming of PET waste into valuable products is largely unexplored.…”
mentioning
confidence: 99%
“…The highest total potential environmental impact (PEI) per kg of lignin was observed to be 0.25 PEI per kilogram using organosolv process; the soda process was 0.02 PEI per kg; the sulfite process was 0.03 PEI per kg, and the Kraft process gave 0.09 PEI per kg of lignin. The soda process offers the lowest pollution with a PEI value of 0.02 per kg, 20 followed by the sulfite process with a value of 0.03 PEI per kg of lignin. Moreover, lignin removal using different pretreatment strategies shows several merits and demerits and their effectiveness varies according to operating conditions 27 .…”
Section: Life Cycle Analysis (Lca) Of Lignin Productionmentioning
confidence: 99%